Faculty of Education Seminar. Robert Crocker. Tape 1 of 2 - Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. Division of Educational Technology, 1989)
Faculty of Education Seminar presentation by Robert Crocker, discussing the report of the Task Force on Mathematics and Science Education and examining his own reaction to the report and its implications. Includes the beginning of the question period following the talk.